Mast cells at the crossroads of microbiota and IBD. Issue 12 (19th November 2018) - De Zuani, Marco; Dal Secco, Chiara; Frossi, Barbara
Abstract: The human gut harbors a wide range of microorganisms that play a fundamental role in the well‐being of their host. A dysregulation of the microbial composition can lead to the development or exacerbation of gastrointestinal (GI) disorders. Emerging evidence supports the hypothesis that mast cells (MCs) play a role in host‐microbiota communication, modulating the mutual influence between the host and its microbiota through changes in their activation state. The ability of some bacteria to specifically affect MC functions and activation has been extensively studied, with different and sometimes conflicting results, while only little is known about MC–fungi interactions. In this review, the most recent advances in the field of MC–bacteria and MC–fungi interactions will be discussed, with a particular focus on the role of these interactions in the onset of GI disorders such as inflammatory bowel diseases (IBD). Moreover, the connection between some MC‐targeting drugs and IBD was discussed, suggesting probiotics as reasonable and promising therapy in the management of IBD patients. Abstract : Host‐microbiota interactions play a fundamental role in human health and intestinal dysbiosis can lead to the development or the worsening of gastrointestinal disorders. Emerging evidences suggest that mast cells, through changes in their activation state, are crucial effectors in the reciprocal influence between the host and its microbiota.